Impact Of Government Support, Access To Finance, And Entrepreneurial Skills On MSME's Growth In Emerging Industrial Clusters - Abidin, Zainal; Purwanto, Edy; Hotifah, Yuliati; Widiyastuti, Ika; Zain, Wafiqotul Karimah (Journal Management & Economics Review (JUMPER), 2025)
This study examines the impact of government support, access to finance, and entrepreneurial skills on the growth of Micro, Small, and Medium Enterprises (MSMEs) operating within emerging industrial clusters. Using a quantitative research design, data were collected from MSME owners and managers through a structured questionnaire, with a total of [insert sample size] valid responses analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The measurement model demonstrated strong reliability and validity, while the structural model revealed that all three factors significantly influenced MSME growth. Access to finance emerged as the strongest predictor (β = 0.362, p < 0.001), followed by entrepreneurial skills (β = 0.298, p < 0.01) and government support (β = 0.254, p < 0.05). The model explained 54.6% of the variance in MSME growth, indicating substantial explanatory power. These findings underscore the necessity of integrated development strategies that combine policy facilitation, financial inclusion, and capacity-building to foster sustainable MSME performance in cluster environments. The study contributes to the resource-based view and institutional theory by demonstrating that both internal capabilities and external enablers are critical for MSME success in emerging economies.